The legacy of the Haldde Observatory - Brekke, Asgeir (History of Geo- and Space Sciences, 2021)
A historical review of the establishment of the Haldde Observatory in Bossekop, Kaafjord, Finnmark, in northern Norway is presented together with some of the scientific outcomes of the efforts and the aftermath of this enterprise that led to the establishment of the University of Tromsø in 1968 and finally the inauguration of the Haldde Observatory as a historic site by the European Physical Society in 2018.